Comparison of reconstructed rapid prototyping models produced by 3-dimensional printing and conventional stone models with different degrees of crowding - Wan Hassan, W.N.; Yusoff, Y.; Mardi, N.A. (Elsevier, 2017)
Introduction: Rapid prototyping models can be reconstructed from stereolithographic digital study model data to produce hard-copy casts. In this study, we aimed to compare agreement and accuracy of measurements made with rapid prototyping and stone models for different degrees of crowding. Methods: The Z Printer 450 (3D Systems, Rock Hill, SC) reprinted 10 sets of models for each category of crowding (mild, moderate, and severe) scanned using a structured-light scanner (Maestro 3D, AGE Solutions, Pisa, Italy). Stone and RP models were measured using digital calipers for tooth sizes in the mesiodistal, buccolingual, and crown height planes and for arch dimension measurements. Bland-Altman and paired t test analyses were used to assess agreement and accuracy. Clinical significance was set at +/- 0.50 mm. Results: Bland-Altman analysis showed the mean bias of measurements between the models to be within +/- 0.15mm(SD, +/- 0.40 mm), but the 95% limits of agreement exceeded the cutoff point of 60.50 mm (lower range, -0.81 to -0.41 mm; upper range, 0.34 to 0.76 mm). Paired t tests showed statistically significant differences for all planes in all categories of crowding except for crown height in the moderate crowding group and arch dimensions in the mild and moderate crowding groups. Conclusions: The rapid prototyping models were not clinically comparable with conventional stone models regardless of the degree of crowding.